2006
DOI: 10.1590/s1413-85572006000100002
|View full text |Cite
|
Sign up to set email alerts
|

Visualização espacial, raciocínio indutivo e rendimento acadêmico em desenho técnico

Abstract: As dificuldades de aprendizagem de Desenho Técnico que experimentam os estudantes de Engenharia relacionam-se com seu nível de aptidão. Para melhorar o processo didático, seria necessário detectar de imediato os estudantes que requerem mais apoio. Este estudo descreve a utilidade de um teste de Visualização Espacial e um teste de Raciocínio Indutivo para prever o rendimento dos estudantes em Desenho Técnico. A amostra foi composta por 484 estudantes do primeiro ano do Curso de Engenharia de quatro centros bras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In RM, calculations transform the persons and item parameters to a unit “measure” ( θ or theta) that is distributed along a continuum. Each unit of measure of θ corresponds to log-odd units or “logits,” a scale with theoretical ranges being ±infinity but typically ranges between ±5 (Prieto & Velasco, 2006), where 0 localizes the average difficulty for the measure. Thus, the RM analysis has the advantage of estimating items’ parameters independently from the participants who enter the sample and providing a robust assessment of construct validity and representation for more consistent scoring and interpretation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In RM, calculations transform the persons and item parameters to a unit “measure” ( θ or theta) that is distributed along a continuum. Each unit of measure of θ corresponds to log-odd units or “logits,” a scale with theoretical ranges being ±infinity but typically ranges between ±5 (Prieto & Velasco, 2006), where 0 localizes the average difficulty for the measure. Thus, the RM analysis has the advantage of estimating items’ parameters independently from the participants who enter the sample and providing a robust assessment of construct validity and representation for more consistent scoring and interpretation.…”
Section: Methodsmentioning
confidence: 99%
“…Infit mean square (Infit MNSQ) and outfit mean square (Outfit MNSQ) are calculated to estimate the model fit to the data, both for items and persons. The infit refers to the weighted MNSQ, providing information about items and possible structural problems (Baker, 2001; Prieto & Velasco, 2006). According to Linacre (2011), infit statistics values between .5 and 1.5 are productive for measurement; values greater than 2.0 can degrade the measurement, values between 1.5 and 2.0 are unproductive for measurement construction, and values smaller than .5 are less productive for measurement but not degrading.…”
Section: Methodsmentioning
confidence: 99%
“…The simple correlation was .62 with Raven’s Advanced Progressive Matrices, .42 with general sequential reasoning, .46 with spatial visualization, and .36 with crystallized intelligence. A latent variable modeling of a general factor using Raven’s Advanced Matrices indicated that the loadings from the Form A and B scales were .86 and .78, respectively (Prieto & Velasco, 2006; Primi, 1998, 2002; Primi, Santos, & Vendramini, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…In Rasch Models, calculations transform the persons and item parameters to a unit "measure" (θ or theta) that is distributed along a continuum, like a ruler. Each unit of measure of θ are log-odd units or "logits", a scale with theoretical ranges being ± infinite, but typically ranges between an amplitude of ± 5 (Prieto & Velasco, 2006), and 0 localizes the average difficulty point set for the measure.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Infit Mean Square (Infit MNSQ) and Outfit Mean Square (Outfit MNSQ) are observed to estimate the fit of the data to the model, both for items and persons. The Infit refers to the weighted mean square, providing information about items and possible structural problems (Baker, 2001;Prieto & Velasco, 2006). According to Linacre (Linacre, 2011), Infit statistics values between 0.5 and 1.5 are productive for measurement; values greater than 2.0 can degrade the measurement; values between 1.5 and 2.0 are unproductive for measurement construction; and values smaller than 0.5 are less productive for measurement, but not degrading.…”
Section: Statistical Analysesmentioning
confidence: 99%